Indoor air quality in rural Southwestern Uganda: particulate matter, heavy metals and carbon monoxide in kitchens using charcoal fuel in Mbarara Municipality - Nakora, Nicholas; Byamugisha, Denis; Birungi, Grace (SN Applied Sciences, 2020)
The use of biomass energy over open fires in sub-Saharan Africa is rampant yet it is associated with air pollution. Information on the contribution of common biomass like charcoal to indoor air pollution in Uganda is scarce; therefore, kitchen-indoor air in charcoal fueled kitchens was characterized for fine particulate matter ( PM2.5), heavy metals and carbon monoxide content in Mbarara Municipality Western Uganda. PM2.5 was measured using University of California Berkeley Particle and Temperature Sensor (UCB-PATS), heavy metals were determined using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) and carbon monoxide was measured using a portable, battery-operated, datalogging Drager Pac 7000. In the kitchens assessed, the mean 24-h concentration for PM2.5 was 0.449 mg/m3 in the wet season and 0.526 mg/m3 in the dry season; CO was 41.52 ppm, and all concentrations were higher than the World Health Organization 24-h Air Quality Guideline for PM2.5 of 0.024 mg/m3 and CO of 6.340 ppm. Heavy metals in particulate matter were in concentration ranges of 1.012–9.820 μg/m3 Fe, 0.012–0.092 μg/m3 Cr, 0.060–10.750 μg/m3 Zn, 0.048–0.300 μg/ m3 Cu, 0.004–0.052 μg/m3 Pb and ND—0.004 μg/m3 Cd. All mean metal concentrations were lower than recommended exposure levels by EPA although chronic exposure is a risk to health. Kitchen ventilation and size were found to significantly influence indoor pollutant levels; charcoal fuel significantly contributed to indoor air pollution and is therefore a risk factor to human health.
Keywords: Charcoal; Carbon monoxide; Indoor air pollution; Particulate matter; Heavy metals